Antithrombotic treatment in stable coronary syndromes: long-term intermittent urokinase therapy in end-stage coronary artery disease and refractory angina pectoris. - Schoebel, F. C. (1997)
Interventions that modify lipid metabolism and blood coagulation have been shown to favourably influence the natural course of coronary artery disease in terms of the primary prevention and treatment of acute cardiovascular events. Various findings suggest that such interventions may also preserve and enhance myocardial perfusion in the chronic stage of the disease. Long-term intermittent urokinase therapy was developed for patients with end-stage coronary artery disease and refractory angina pectoris. A dose of 500,000 IU of urokinase given intravenously as a bolus three times a week for of 12 weeks reduced symptoms by 70% and was accompanied by objective improvements in myocardial perfusion and an increase of ergometric exercise capacity. The possible therapeutic mechanisms of long-term intermittent urokinase therapy-improvement of rheological blood properties mediated by fibrinogen reduction, thrombolysis of non-occlusive subclinical thrombi, and regression of atherosclerotic plaques-are discussed in the context of other antithrombotic approaches.